2016
DOI: 10.2174/1568026616666160204122449
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Role of Natural Polyphenols

Abstract: Neurodegenerative diseases cause a progressive functional alteration of neuronal systems, resulting in a state of dementia which is considered one of the most common psychiatric disorders of the elderly. Dementia implies an irreversible impairment of intellect that increases with age causing alteration of memory, language and behavioral problems. The most common form, which occurs in more than half of all cases, is Alzheimer's disease, characterized by accumulation of amyloid plaques and neurofibrillary tangle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
56
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(58 citation statements)
references
References 0 publications
0
56
0
2
Order By: Relevance
“…Physical exercise and healthy diets have been reported to have implications to delay disease progression of Alzheimer’s disease (AD) in elderly individuals and improved cognitive functions in subjects with mild cognitive impairment and early AD patients [3, 4]. There are a large number of natural products and herbs currently available, including curcumin, green tea and vitamin C, vitamin E, beta carotene, Gingko Biloba, Ginseng, Rosemary, Sage, and many others [13].…”
Section: Introductionmentioning
confidence: 99%
“…Physical exercise and healthy diets have been reported to have implications to delay disease progression of Alzheimer’s disease (AD) in elderly individuals and improved cognitive functions in subjects with mild cognitive impairment and early AD patients [3, 4]. There are a large number of natural products and herbs currently available, including curcumin, green tea and vitamin C, vitamin E, beta carotene, Gingko Biloba, Ginseng, Rosemary, Sage, and many others [13].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, polyphenols have emerged as promising therapeutic candidates due to their impressive antioxidant, antineuroinflammatory, and antiapoptotic effects (reviewed by [7]). In particular, anthocyanins, a unique class of flavonoid compounds, show significant potential as a treatment for neurodegenerative disease for these reasons in addition to the observation that they are among the most commonly consumed polyphenolic species around the world [8].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that natural phytochemicals, such as resveratrol, curcumin, apigenin, and epigallocatechin gallate, could suppress LPS‐induced neuroinflammation and amyloidogenesis, and thus improve learning and memory impairment (11). Chicoric acid (CA), a caffeic acid derivative, existing extensively in echinacea (also known as purple coneflower; Echinacea purpurea ), chicory, lettuce, dandelion, and other edible plants and vegetables, has been regarded as a nutraceutical that has powerful antioxidant, anti‐HIV, and antiobesity activities (12, 13).…”
mentioning
confidence: 99%